Sex and gender identifications in the view of Islam and western thought: a comparative narrative on gender ambiguity debates - Mahmad Robbi, Ahmad Akram; Muhsin, Sayyed Mohamed; Mohiuddin, Mohammad; Md. Sawari, Mohd. Fuad; Jamaludin, Khairul Fahmi (Universiti Sains Islam Malaysia, 2025)
Contemporary debates on gender identity reveal a fundamental divergence between Islamic and Western perspectives, creating significant theoretical and practical tensions in addressing gender ambiguity. Islam upholds a binary framework where biological sex determines gender identity, while Western thought increasingly separates sex from gender, recognizing gender as a social construct independent of biological markers. This ideological divide raises critical issues regarding gender dysphoria management, gender transition legitimacy, and accommodation of gender-variant individuals within different societal frameworks. This study conducts a comparative analysis of Islamic jurisprudence and Western gender theory through qualitative content analysis of religious texts, scholarly works, medical literature, and policy documents to examine how each tradition addresses gender identification conflicts. The research investigates theoretical foundations and practical applications of both approaches to gender-related disorders and identity crises. Key findings reveal that while Islam maintains consistent binary classifications rooted in biological determinism since the Quranic era, it demonstrates flexibility in addressing intersex conditions through established jurisprudential mechanisms. Despite fundamental philosophical differences, the study concludes that potential convergence areas exist between Islamic principles and certain medical interventions, suggesting possibilities for nuanced dialogue rather than absolute opposition in addressing contemporary gender identity challenges and fostering cross-cultural understanding